A new Age of Extremes? : Anti-political Politics and Identity Remaking in the early 21st Century - da Silva, Jamile Borges; Figueiredo, Fábio Baqueiro; Gomes, Patricia Godinho (Institute of African Studies, 2023)
We are keenly interested in understanding how the “glocal” scene intervened in the ways of doing politics, and how strategies of political reproduction of longestablished oligarchies and autocracies could present themselves as absolutely new and antipolitical, claiming for radical reforms in the realms of economy, society, culture and education. India, the Philippines, Kenya, Burkina Faso, Mozambique, Germany, Italy, Colombia, Suriname and Brazil were chosen as empirical cases.
Keywords: Antipolitical politics; Political imagination; Political mobilization; Populism; Neo-Liberalism; Identity; Inequality; Nation Building; Ethnicity; Race; Media